KEPUTUSAN MAJELIS ULAMA INDONESIA TENTANG PEMIMPIN YANG DIPILIH - Rastana Dermayu; Adang Djumhur Salikin; Wasman Wasman (UIN Siber Syekh Nurjati Cirebon, 2020)
Â ABSTRACTThe decision of the Indonesian Ulema Council in 2009 in accordance with Law number 39 of 1999 concerning human rights article 43 and Law number 12 of 2005 concerning Ratification of the Covenant on Civil Civil Rights Article 25. In this case the MUI is moderate. The decision of the Indonesian Ulema Council in 2016 regarding the chosen leader stated QS. Al-Ma'idah verse 51 explicitly forbids making Jews and Christians as leaders and the proposition forbids making non-Muslims as leaders. And scholars are required to convey the contents of surah al-Ma'idah verse 51 as an obligation to choose Muslim leaders and believe in the truth of the contents of surah al-Ma'idah verse 51 as a guide in choosing leaders. That is because the MUI